2021
DOI: 10.3389/fphar.2020.621099
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neurological Manifestations of Coronaviruses by Candidate Phytochemicals: A Mechanistic Approach

Abstract: The novel coronavirus 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made a wide range of manifestations. In this regard, growing evidence is focusing on COVID-19 neurological associations; however, there is a lack of established pathophysiological mechanisms and related treatments. Accordingly, a comprehensive review was conducted, using electronic databases, including PubMed, Scopus, Web of Science, and Cochrane, along with the author’s expertize in COVID-19 associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 266 publications
(339 reference statements)
0
17
0
Order By: Relevance
“…The present study shows that alkaloids, as one of the most widespread natural compounds, hold out the hope for an effective treatment against COVID-19, due to their simultaneous effects on several therapeutic targets with prominent antiviral effects. Hence, marine/plant-derived alkaloids such as berberine, tetrandrine, cepharanthine, lycorine, ergotamine, crambescidin 786, palmatine, noscapine, and quinine with prominent anti-SARS-CoV-2 effects along with antipyretic, anti-inflammatory, antitussive and lung injury, immunomodulatory, and protective effects against neurotoxicity, cardiotoxicity, nephrotoxicity, and hepatotoxicity could be promising candidates for COVID-19 treatment [ 46 , 48 , 52 , 64 , 68 , 76 , 77 , 79 , 82 , 93 ]. Therefore, according to the contents mentioned, extensive and comprehensive clinical studies on these compounds seem to be useful and necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study shows that alkaloids, as one of the most widespread natural compounds, hold out the hope for an effective treatment against COVID-19, due to their simultaneous effects on several therapeutic targets with prominent antiviral effects. Hence, marine/plant-derived alkaloids such as berberine, tetrandrine, cepharanthine, lycorine, ergotamine, crambescidin 786, palmatine, noscapine, and quinine with prominent anti-SARS-CoV-2 effects along with antipyretic, anti-inflammatory, antitussive and lung injury, immunomodulatory, and protective effects against neurotoxicity, cardiotoxicity, nephrotoxicity, and hepatotoxicity could be promising candidates for COVID-19 treatment [ 46 , 48 , 52 , 64 , 68 , 76 , 77 , 79 , 82 , 93 ]. Therefore, according to the contents mentioned, extensive and comprehensive clinical studies on these compounds seem to be useful and necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, inhibition of nucleotide biosynthesis was suggested for the aforementioned antiviral effects [ 51 ]. In addition to its anti-SARS-CoV-2 effects, lycorine also has prominent neuroprotective effects that can play a multifaceted role in the treatment of this disease due to the neurological complications of COVID-19 disease [ 52 , 53 ]. Consequently, Bleasel and Peterson published a commentary on the potential of emetine and ipecac alkaloids as anti-SARS-CoV-2 agents [ 54 ].…”
Section: Alkaloids As Potential Phytochemicals Against Sars-cov-2mentioning
confidence: 99%
“…The potential of phytochemicals in demonstrating antiviral effects through inhibiting the viral life cycle indicates a promising future to find novel antiviral lead compounds against neuronal signs of emerging viral diseases. Previously, we have analyzed the capability of these phytochemicals in passing BBB towards neuroprotective responses ( Fakhri et al, 2020b ), which showed hopeful results for most plant-derived secondary metabolites in modulating the aforementioned dysregulated pathways in CNS. Additionally, to drawback, the pharmacokinetic limitation of phytochemicals, novel drug delivery systems, could pave the road towards neuroprotection against emerging viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently scientists investigated the effects of natural products on emerging infectious diseases, including the influenza virus, DENV, Zika, and EBOV ( Zheng et al, 2021 ). Considering the common dysregulated pathophysiological mechanisms of emerging infectious diseases and the capability of some phytochemicals in passing BBB ( Fakhri et al, 2020b ) urge the need to introduce candidate phytochemicals as potential modulators of peripheral complications, extrapolated to the same dysregulations in CNS.…”
Section: Phytochemicals Against Emerging Infectious Diseases: Mechanistic Approaches To Neurological Signsmentioning
confidence: 99%
“…TBI induced mitochondrial neuronal damage, as evidenced by an increase in ROS mitochondria and a reduction in MMP, causing the previous mitochondrial transition pore to open [ 69 ]. Polydatin has shown various pharmacological benefits, including antioxidation, anti-inflammation, anti-apoptosis, and brain-associated injuries [ 71 , 72 ].…”
Section: Polydatin Against Nddsmentioning
confidence: 99%